2021
DOI: 10.1111/cch.12892
|View full text |Cite
|
Sign up to set email alerts
|

Are healthcare providers and young people talking about sexuality? A scoping review to characterize conversations and identify barriers

Abstract: Background Conversations about sexuality with healthcare providers (HCPs) are critical to youth's positive development, including youth with disabilities or chronic conditions. Yet, little is known about the characteristics of sexuality conversations with youth in healthcare settings. This scoping review examined the nature and extent of sexuality conversations between HCPs and youth (with and without a disability or chronic condition) and aimed to identify barriers to these conversations. Methods Scoping revi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 69 publications
(190 reference statements)
0
2
0
Order By: Relevance
“…Indeed, professionals may provide young individuals with appropriate guidance regarding sexuality (e.g., sexual pleasure [90]), clarify any misconceptions about it, and offer gender-sensitive support [91]. However, barriers to professional-young person discussions about sexuality include a lack of initiative, perceived judgment, lack of awareness, and presumed feelings of shame [92,93].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, professionals may provide young individuals with appropriate guidance regarding sexuality (e.g., sexual pleasure [90]), clarify any misconceptions about it, and offer gender-sensitive support [91]. However, barriers to professional-young person discussions about sexuality include a lack of initiative, perceived judgment, lack of awareness, and presumed feelings of shame [92,93].…”
Section: Discussionmentioning
confidence: 99%
“…Prior research has found that key barriers to parent–child communication about sexuality include limited parental sexual knowledge; parental beliefs that young people are not ready to learn about sex; discomfort; and cultural factors, such as gender, race, and religion (Malacane & Beckmeyer, 2016). In the case of health care providers, barriers include personal discomfort; perceiving their patients to have a limited knowledge base; and issues establishing confidentiality (Lung et al, 2021).…”
Section: Lack Of Sexuality Communication Contributes To Significant H...mentioning
confidence: 99%